Pemodelan Arsip Novel Berdasarkan Klaster Data dan Penyaringan - Awangga, Rolly Maulana; Pane, Syafrial Fachri; Kurniawan, Cahya (Technomedia Journal, 2020)
File archiving now needs to be appropriately managed so that it is easy to find and manage. File archiving in question is how to help in the process of finding data with a considerable number, to facilitate the work following the aim to reduce the time the search data can be integrated with the system created. Archiving itself aims to facilitate the management of data that is very diverse and with a large amount, to facilitate the management and also the control carried out. The problem with filing archives, in this case, is the lack of management regarding the correct filing of archives. Controlled archive file management makes the amount of time that is passed only by searching files. By looking at large amounts of data, it is necessary to use methods to be able to manage and search, with Alphabet, Numeric and K-means Clustering methods designed and processed, it is easier to manage existing data searches so that the work doesn't take too much time. There needs to be further development of the analysis carried out at this time to further improve the effectiveness by creating a system following the analysis rules made at this time. Keywords: Filing, Archives, File Management Alphabetical Filling System, Numerical Filing System, K-means Clustering.